2022
DOI: 10.1186/s12891-022-05223-x
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for cementless primary stem in hip arthroplasty for early or late fixation failures of intertrochanteric fractures?

Abstract: Background The choice of femur stems during the hip arthroplasty procedures for patients with treatment failure of intertrochanteric fractures (ITF) remains controversial. We aimed to compare the surgical complication and reoperation rates between cementless primary and revision stems in the early (≤3 months) and late (> 3 months) fixation failures of ITF. Methods This was a retrospective, cohort study conducted in a single, tertiary referral ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…3 When using a cementless femoral stem, primary stability is of paramount importance but can be challenging, owing to varying degrees of bone loss. 4,5 One advantage of using a primary stem during the revision procedure is easier implantation, sparing the diaphysis invasion while preserving the native bone stock. 6,7 In contrast, the benefits of using a longer, revision stem include an increased contact area for osteointegration, which allows bypass of the metaphysis and achieves a more reliable fixation in the diaphysis.…”
Section: Introductionmentioning
confidence: 99%
“…3 When using a cementless femoral stem, primary stability is of paramount importance but can be challenging, owing to varying degrees of bone loss. 4,5 One advantage of using a primary stem during the revision procedure is easier implantation, sparing the diaphysis invasion while preserving the native bone stock. 6,7 In contrast, the benefits of using a longer, revision stem include an increased contact area for osteointegration, which allows bypass of the metaphysis and achieves a more reliable fixation in the diaphysis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported different types of the femoral prosthesis in CHA for FIF-ITF patients, as well as cemented [13][14][15] , cementless [16][17][18][19] , standard 14,17,20 , calcar-replacement 5 , modular [21][22][23] , nonmodular 24 , revision stem 25,26 , etc. Few studies have paid attention to the length of the femoral prosthesis, this study retrospectively included and analyzed the results, technical problems, and complications of CHA following FIF-ITF patients in multi-centers, and the clinical e ciency of standard and long stems were compared.…”
Section: Introductionmentioning
confidence: 99%